2015
DOI: 10.3109/09638237.2015.1022250
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the magnitude of the associations between eating disorders symptoms and depression and anxiety symptoms. Results from a community sample of adolescents

Abstract: Our results show an urgent need to address EDs prevention in adolescent girls and boys from the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Both sexes demonstrate similar levels of cognitive inflexibility, elevated perfectionism, and have similar age of onset, weight at initial treatment presentation, and prognosis (Fernández‐Aranda et al, ; Goddard, Carral‐Fernandez, Denneny, Campbell, & Treasure, ; Welch, Ghaderi, & Swenne, ). Men and women with EDs demonstrate similar patterns of association between disordered eating symptoms and symptoms of generalized anxiety and depression (Sidor, Baba, Marton‐Vasarhelyi, & Chereches, ).…”
Section: Sex Disparitiesmentioning
confidence: 98%
“…Both sexes demonstrate similar levels of cognitive inflexibility, elevated perfectionism, and have similar age of onset, weight at initial treatment presentation, and prognosis (Fernández‐Aranda et al, ; Goddard, Carral‐Fernandez, Denneny, Campbell, & Treasure, ; Welch, Ghaderi, & Swenne, ). Men and women with EDs demonstrate similar patterns of association between disordered eating symptoms and symptoms of generalized anxiety and depression (Sidor, Baba, Marton‐Vasarhelyi, & Chereches, ).…”
Section: Sex Disparitiesmentioning
confidence: 98%
“…Recent epidemiological research has shown that prevalence of EDs among adolescents is estimated to be 0.3% for anorexia nervosa (AN), 0.9% for bulimia nervosa (BN), and 1.6% for binge eating disorder (BED) 13,14. Notwithstanding an increase of incidence of EDs in adolescent males over the last few decades,15 EDs predominantly affect female adolescents, with a rate of 5.7% for girls versus 1.2% for boys;16 moreover, adolescent girls usually show more severe symptoms of AN, BN, and BED if compared to same-age boys 17…”
Section: Introductionmentioning
confidence: 99%
“…There have been no reports on the association between Bmi and depression in patients with CF. The literature mainly contains reports on the relationship between depression and overweight/ /obesity or anorexia [21,22]. in patients with cystic fibrosis, Bmi is a measure of physical well-being and good health control.…”
Section: Discussionmentioning
confidence: 99%